Ann Agee Photograph of Library Notice - Agee, Ann::::::::: (2022)
A photograph of the Dr. Martin Luther King Jr. Library entrance with a notice of the library's closure posted on the door. One of seven photographs Ann Agee took of the joint public/university library during the beginning of the COVID-19 pandemic.